Results of linear effects models examining factors which influenced Travis Kelce’s performance in the Pre-Swift era (2014-2022). - James M. Smoliga (9074225) (2025)
Chiefs’ pre-game Elo was the only predictor that was entered into the model. Opponent Elo score, Chief’s win probability, and home/away game status were not selected for inclusion in the final model.